Surgical Correction of Astigmatism (Springer International Publishing, 2018)
This book offers a state of the art review of the surgical techniques that can be employed for the management of astigmatism, with the aim of providing a clear, comprehensive, step-by-step guide that will help practitioners to optimize outcomes in daily practice. The book is divided into two sections covering cutting-edge surgical approaches in cataract and refractive patients. In addition to describing options including incisional techniques, toric intraocular lenses, and femtosecond laser technology, the cataract section identifies key points in preoperative evaluation and examines the clinical impact of the most recent relevant clinical research. The refractive section explains the fundamentals of excimer laser treatment and discusses the clinical results achieved with different laser platforms. In addition, specific attention is devoted to surgical management of astigmatism after penetrating keratoplasty The authors are renowned experts who offer the benefit of many years of clinical experience and highlight pearls that will help readers to replicate their results. Supplementary videos of informative sample cases are included to further aid everyday practice.